O advento da metafísica da duração e a crítica de Bergson ao positivismo - Penna, Eliza Sophia D. A. Jorge (2019)
The present work aims to discuss the context in which Henri Bergson 's critique of positivism of the late 19th and early 20th century arises and the importance of metaphysics of duration in the History of Philosophy. From Time and free Will (D.I.), first published in 1889, we set out to reflect on the differences established by Bergson between space and time, culminating in the discussion of the free act and the time of consciousness. The conclusions of D.I. approach the metaphysical philosophy of nascent existentialism at the time, not only in France but also in Germany. This approach was taken into account in the preparation of the present study, which is essentially bibliographic. After the presentation of the historical context and the criticism proper in the first work of Bergson, this study was devoted to pointing out, finally, how the metaphysics of duration represents a rereading of Aristotelian metaphysics capable of expanding the possibilities of searching for ontological foundation of existence